EKSPERIMENTASI MODEL PEMBELAJARAN GROUP INVESTIGATION (GI) DAN THINK TALK WRITE (TTW) DENGAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK PADA MATERI RELASI DAN FUNGSI DITINJAU DARI KREATIVITAS BELAJAR SISWA KELAS VIII SEMESTER 1 SMP N DI KABUPATEN SRAGEN - Sari, Rahmita Ika; Budiyono, Budiyono; Subanti, Sri (Jurnal Pembelajaran Matematika, 2014)
Abstract: The objectives of this research were to find out: (1) which students had the better mathematics learning achievement, those treated with direct learning, those with GI with PMR or those with TTW with PMR approach, (2) which students had the better mathematics learning achievement, those with high or medium or low learning creativity, (3) in each learning creativity, which students had the better mathematics learning achievement, those treated with direct learning, those with GI with PMR or those with TTW with PMR approach, and (4) in each learning model, which students had the better mathematics learning achievement, those with high or medium or low learning creativity. This research was a quasi experimental research employing 2 independent variables (learning model and learning creativity) and 1 dependent variable (mathematics learning achievement). The population of research was all of the VIII graders of Public Junior High Schools in the school year of 2013/2014. The sampling technique used was Stratified Cluster Random Sampling. The sample students consisted of three schools: SMP Negeri 1, SMP Negeri 6 and SMP Negeri 2 Karangmalang Sragen. The proposed hypotheses of the research were tested by using the two-way analysis of variance (ANAVA) with unbalanced cells with the factorial design of 3 x 3. The results of research were as follows: (1) the students treated with direct learning model had learning achievement as good as those with GI learning model with PMR approach, those with TTW learning model with PMR approach had learning achievement better than those with direct learning, while those with TTW with PMR had learning achievement as good as those with GI learning model with PMR approach, (2) the students with high learning creativity had learning achievement as good as those with medium one, those with high and medium learning creativity had learning achievement better than those with low one, (3) in each learning creativity level, the students treated with direct learning model had learning achievement as same as those with GI learning model with PMR approach, those with TTW learning model with PMR approach had learning achievement better than those with direct learning, and those with TTW with PMR had learning achievement as same as those with GI learning model with PMR approach, (4) in each learning model, the students with high learning creativity had learning achievement as same as those with medium one, those with high and medium learning creativity had learning achievement better than those with low one.Keywords: Group Investigation (GI), Think Talk Write (TTW), Realistic Mathematics Education approach, Learning Creativity.